Child Vulnerability and Well-being among Farmer Families - Danisya Primasari; Herien Puspitawati (Journal of Family Sciences, 2016)
This research aimed to identify vulnerability and well-being of children in a family of farmers, identify the typology of vulnerability and well-being of children in the family of farmers, and analyze the relationship between family characteristics, characteristics of children with the vulnerability and well-being of children. The population in this research is family farmers who have children of 4 and 5th grade who reside in the village Sindangjaya, District Cipanas, Cianjur with a sample of 35 children. Sampling was conducted using probability sampling method with random sampling techniques. The results showed that the internal susceptibility to family farmers is low, relatively low external vulnerability, and low well-being. Typology vulnerability of children and the well-being of children in a family of farmers included in Type 1 and Type 4. There was a significant negative correlation between family size and order of the child with the child's welfare, but there was no significant relationship between the characteristics of families and children with children's vulnerability.